Determinants of exchange rate in Malaysia / Nur Farhanis Syafiqah Muhamad Fazli - Muhamad Fazli, Nur Farhanis Syafiqah (Faculty of Business and Management, 2020)
The purpose of this study is to examine the determinants of Exchange Rate (EXR) in Malaysia. The determinants with Interest Rate (INT), Inflation (INF), Balance of Payment (BOP), Foreign Direct Investment (FDI) and Government Debt (GVD). The study was using time series data from 2009 to 2018 quarterly. Multiple linear regression model has been used in this study. The result shows that Inflation Rate and Government Debt have positive and negative significant relationship towards Exchange Rate in Malaysia. Meanwhile, there is insignificant relationship between Interest Rate, Balance of Payment, and Foreign Direct Investment on Exchange Rate in Malaysia. It means Interest Rate, Balance of Payment, and Foreign Direct Investment has no significant effect on Foreign direct investment in Malaysia. Thus, other researcher can used more than 40 observation in future to get more accurate result that depends on Malaysia’s condition.